The Effect Of Moral Integrity, Lifestyle And Organizational Culture On Anti-Corruption Intention - Putri, Dhiny Aditama; Nihayah, Zahrotun (‎‎‎TAZKIYA: Journal of Psychology, 2017)
This study aims to examine the effect of moral integrity, lifestyle and organizational culture on anti-corruption intention involving 54 police officers and 97 civil servants of police in police institution X. Sampling technique in this study using non-probability sampling. The measuring tool used in this study consists of the Anti Corruption Intelligence Scale which the authors develop themselves to measure the anti-corruption intention, Moral Integrity Scale to measure moral integrity, AIO Psychographic to measure lifestyles, and the Denison Organizational Culture Survey to measure organizational culture. Confirmatory Factor Analysis (CFA) was used to test the validity of measuring instrument and Multiple Regression Analysis is used to test the research hypothesis. The results revealed that there was a significant of moral integrity, lifestyle and organizational culture against anti corruption intention at 56.3%. It means that the proportion of varians of anti-corruption intention in can be explained by moral integrity, lifestyle, and organizational culture at 56.3% and 43.7% explored by other factors.  DOI:10.15408/tazkiya.v22i2.8413